Timing of school tracking as a determinant of intergenerational transmission of education - Bauer, Phillipp; Riphahn, Regina Therese (Economics letters, 2006)
This paper applies data from Switzerland to test the hypothesis that intergenerational educational mobility is affected by the time at which pupils are first segregated in attainment related tracks in secondary school. The time of tracking significantly affects intergenerational mobility. Late tracking reduces the relative advantage of children of better educated parent
WiSo-Import:2015-03-26:2654
Keywords: ability tracking; streaming; segregation; intergenerational transmission of education; social mobility; educational mobility; socioeconomic gradient